Pupils' perceptions on the contemporary literature programme:a case study / Siti Maizura Abd Raffur - Abd Raffur, Siti Maizura (2010)
The main aim of this study is to investigate pupils' perception on contemporary literature in ESL classroom. The study involved a group of primary school pupils at one of the primary schools in Gombak District. The study employed a questionnaire to 60 pupils and a set of interview questions to 10 pupils. The questionnaire required respondents to respond to items based on a four-point Likert scale, ranging from a score of 1 which indicated 'strongly disagree' to a score of 4 which indicated strongly agree. There were four aspects presented in the questionnaire. They were an aspect on pupils' perception on contemporary literature, benefits of learning literature, the methods and approaches used in teaching literature and pupils' perception on literary texts. The quantitative data collected was analysed using SPSS 13.0 for descriptive statistics while the interview data was analysed inductively and deductively before final conclusions were made. The findings indicated that even though the pupils were unhappy learning literature in ESL classroom, they were moderately convinced that learning literature is beneficial. The findings also indicated that the pupils are not satisfied with the materials and approaches used in the literature classroom. However, the pupils also indicated that they like to read about different cultures and values and they are happy with the themes presented in the reading texts. This study seems to suggest that learning literature provokes different perceptions but with the appropriate teaching methods, strategies and literary texts, the passion to read literary texts and studyliterature would be a life-long reward.